Studying the Golden Generations' Effects and the Changes in the Competitive Balance of the Portuguese Soccer League - Cima, C.; Mourão, P. (International Journal of Sport Finance, 2015)
Competitive balance is recognized as an important source of market efficiency, a fact found to be true of soccer markets, studied here. In this paper, we measure the competitive balance of the Portuguese Soccer League “Primeira Liga” using data compiled since the 1980/1981 season. Employing different measures of competitive balance, we test for trends in competitive balance using the most appropriate (considering that we are working with time series) techniques and explore how this trend had changed because of the existence of the Golden Generation of soccer players (e.g., Figo, Rui Costa, or Joao Vieira Pinto). We conclude that competitive balance in the Portuguese Soccer League does not exhibit a regular trend and that the Golden Generation contributed to more balanced seasons. This finding has several important implications, among them the need for Portuguese soccer leagues to increase competitive balance to ensure the sustainability of soccer wages, revenues and profits by putting special effort into the development of highly-skilled, young soccer players.